The use of oxidized lignin as a bio-based plasticizer for mortar and concrete - Dorneles de Mello Matheus; Vormoor Michaela; Poukka Outi; Fearon Olesya; Suurnakki Anna; Vyorykka Jouko (MATEC Web of Conferences)
Plasticizers are widely utilized in construction to enhance material performance by improving cement particle dispersion through adsorption and stabilization. This modification alters concrete’s rheological properties, enhancing flowability and reducing water demand, resulting in a final product with superior strength and durability. The growing demand for sustainable solutions in the plasticizer market presents an opportunity for developing new chemistries. Oxidized lignin, a biobased material synthesized under alkali-O2 conditions, has demonstrated promising plasticizing properties in concrete. This study benchmarks oxidized lignin against conventional plasticizers, evaluating their performance in fresh and hardened mortar, including workability, setting time, density, and compressive strength. Additionally, the tunability of oxidized lignin is explored concerning end-use properties. The environmental benefits of using a biobased plasticizer are also considered, highlighting its potential to reduce the carbon footprint of concrete production. Future research directions include optimizing the synthesis process to enhance performance further.